Geographical potentials of dark tourism in Dukan district - احمد, ئامانج جلال احمد; رشید, آ.د. شیروان عمر رشید; Mohammed, Adnan Ali Mohammed (Sulaimani Journal for Humanities, 2025)
This research is an attempt to define "Dark Tourism," which is a type of tourism associated with death and suffering; as the term dark tourism is a new term in academia. Therefore, in this research, we attempted to shed light on the concept of dark tourism and its emergence, as well as the objectives, reasons, and motivations behind the interest in this type of tourism known as dark or black, due to its connection with the dark and tragic aspects of humanity such as death, suffering, and violence..The First Anfal Campaign (Anfal of Jafayati Valley - carried out from February 22 to March 19, 1988), this campaign began with an attack on the villages of (Sargalu and Bargalu) in Jafayati Valley and extended from Bingird to the east of Dukan Lake and Dukan town, from there it included the towns of Mawat andChwarta. The aim of this attack was to destroy and demolish 25 to 30 villages in Jafayati Valley. The latest heavy weapons were used, which caused massive destruction in these areas. Most of the area's residents were subjected to the attack, some managed to escape and survive, while others were arrested by the army and disappeared. This is considered one of the most tragic catastrophes in modern history. The Anfal Monument in the center of Dukan district and the remnants of this catastrophe in the villages of the region stand as witnesses to the narrative of the tragedy that befell the residents of the area. The research hypothesis is based on the presence or absence of dark tourism activities in the study area. In conclusion, we found that this type of tourism has not received attention and importance alongside other tourism activities in the study area, and the Anfal Monument has not been utilized as a source for attracting tourists.
Keywords: Dark Tourism; Dukan District; Anfal; Weapons of Mass Destruction; Anfal Monument; Ethnic Cleansing